A STUDY ON EXTRACTION PROCESS AND IN VITRO ANTIOXIDANT ACTIVITY OF TOTAL PHENOLS FROM RHIZOMA IMPERATAE - Zhou, Xian-rong; Wang, Jian-hua; Jiang, Bo; Shang, Jin; Zhao, Chang-qiong (African Journal of Traditional, Complementary and Alternative Medicines, 2013)
The study investigated the extraction method of Rhizoma Imperatae and its antioxidant activity, and provided a basis for its rational development. The extraction method of Rhizoma Imperatae was determined using orthogonal design test and by total phenol content, its hydroxyl radical scavenging ability was measured by Fenton reaction, and potassium ferricyanide reduction method was used to determine its reducing power. The results showed that the optimum extraction process of Rhizoma Imperatae was a 50-fold volume of water, 30 ℃, three times of extraction with 2 h each. Its IC50 for scavenging of hydroxyl radicals was 0.0948 mg/mL, while IC50 of ascorbic acid was 0.1096 mg/mL; in the ferricyanide considerable reduction method, the extract exhibited reducing power comparable to that of the ascorbic acid. The study concluded that Rhizoma Imperatae extract contains relatively large amount of polyphenols, and has a good anti-oxidation ability.